Pemanfaatan Material Pasir Sebagai Bahan Pengganti Fraksi Agregat Halus Untuk Lapis Pondasi Agregat Kelas A - Santoso, Muhammad Bagus; Putra, Sasana; Sulistyorini, Rahayu; Herianto, Dwi (Universitas Lampung, 2023)
The base course material uses mountain stone which is broken up with a stone crusher so that it has a high quality which makes it expensive. In this research we need an alternative material to replace fine aggregate that meets the specification requirements. One of the more affordable resources is sand aggregate. The purpose of this study was to determine the density and comparison of the California Bearing Ratio (CBR) value of the base course using sand as a substitute for fine aggregate. The method used in this research is laboratory scale testing to obtain data on aggregate characteristics, optimum moisture content, and CBR values. The base course aggregate mixture used was 55% coarse aggregate and 45% fine aggregate consisting of a mixture of fine crushed stone and 0%, 10%, and 20% sand substitution. The results showed that the KAO value decreased with the addition of sand aggregate. Laboratory CBR values increased with 0% sand substitution having a CBR value of 99.2%, 10% sand substitution having a CBR value of 90.6%, and 20% sand substitution having a CBR value of 84.1%. Only the laboratory CBR value with sand substitution of 20% does not meet the specifications for base A aggregate, namely a minimum value of 90%.